Near-surface heat transfer at two gentle slope sites with differing aspects, Qinghai-Tibet Plateau - Fan, Xingwen; Lin, Zhanju; Niu, Fujun; Lan, Aiyu; Yao, Miaomiao; Li, Wenjiao (Frontiers in Environmental Science, 2022)
The slope aspect effect is widely distributed on the Qinghai-Tibet Plateau and has an important impact on the permafrost environment. The differences in surface heat exchange characteristics of different slope aspects in the permafrost region of Gu Mountain in the Beiluhe Basin were compared and analyzed based on observations of the south slope (sunny slope) and north slope (shadowy slope) from 2019 to 2021. The air-ground heat transfer process on the slopes was simulated using the Monin-Obukhov similarity theory. Then, the simulation results of the sensible and latent heat fluxes on the slopes were corrected and analyzed using the Bowen ratio correction method. The results show that under the influence of the solar altitude angle and subsurface conditions, the downward shortwave radiation (DR), upward shortwave radiation (UR), and upward longwave radiation (ULR) were higher on the sunny slope than those on the shadowy slope, whereas the downward longwave radiation (DLR) was lower than that on the shadowy slope. Jointly, the net radiation energy on the sunny slope was smaller than that on the shadowy slope, and the annual average net radiation difference reached 16.7 W·m−2. The annual and daily variations in soil heat flux on the sunny slope were higher than those on the shadowy slope. The energy closure rate on the sunny slope was high with a confinement rate of 0.85, whereas that on the shadowy slope was poor with a confinement rate of 0.51. The air-ground energy transfer patterns on the sunny and shadowy slopes showed obvious seasonal differences. Both slopes are dominated by the sensible heat exchange transfer mode in the cold season, whereas the shadowy slope is dominated by latent heat exchange in the warm season. This study improves our understanding of the distribution, development, and environmental effects of permafrost, under the influence of local factors.